TRANSFORMASI USAHA KERUPUK PULI “KARYA EMAS” MELALUI TEKNOLOGI PRODUKSI, INOVASI PRODUK, DAN PEMASARAN DIGITAL - Syunu Trihantoyo; Ali Hasbi Ramadani; Dian Citaningtyas Ari Kadi; Fransisca Bella Oktaviana; Adinda Maulita Salsabilla; Sumiati Sumiati (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACT Micro, small, and medium enterprises (MSMEs) based on local food products play an important role in supporting rural economic development; however, they still face various constraints in production, financial management, and marketing aspects. The main problems identified in the “Karya Emas” Kerupuk Puli business group in Simbatan Village include low production capacity due to manual processing, inadequate financial record-keeping, and limited market access caused by minimal utilization of digital technology and weak product branding. This community engagement program aims to enhance the business capacity through an integrated empowerment approach covering production, financial management, product innovation, and digital marketing. The implementation method consists of several stages, including socialization and focus group discussion (FGD), business management training, production training using appropriate technology, digital marketing training, implementation of a kerupuk puli molding machine, as well as mentoring and evaluation based on performance indicators. The results show a significant increase in production capacity from approximately 20 to 80 packs per day with a 60% improvement in production efficiency. The partners are also able to conduct simple financial recording, calculate production costs, and separate business and household finances. In addition, brand identity and more informative packaging have been developed, along with the utilization of social media and marketplace platforms for marketing. Furthermore, product innovation in the form of a fish-flavored variant has been successfully developed to increase competitiveness. Overall, this program effectively improves productivity, strengthens business governance, and expands market access for local food MSMEs. The integrated empowerment model is expected to provide a sustainable solution for rural-based MSME development. ABSTRAK Usaha mikro kecil menengah (UMKM) berbasis pangan lokal memiliki peran penting dalam mendukung perekonomian desa, namun masih menghadapi berbagai keterbatasan pada aspek produksi, manajemen, dan pemasaran. Permasalahan utama pada Kelompok Usaha Kerupuk Puli “Karya Emas” di Desa Simbatan meliputi rendahnya kapasitas produksi akibat proses manual, belum optimalnya pencatatan keuangan usaha, serta terbatasnya akses pasar karena minimnya pemanfaatan teknologi digital dan belum adanya penguatan branding produk. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas usaha melalui pendekatan pemberdayaan terpadu yang mencakup aspek produksi, manajemen, dan pemasaran digital. Metode pelaksanaan dilakukan melalui tahapan sosialisasi dan FGD, pelatihan manajemen usaha, pelatihan produksi berbasis teknologi tepat guna, pelatihan pemasaran digital, penerapan mesin pencetak kerupuk puli, serta pendampingan dan evaluasi berbasis indikator kinerja. Hasil kegiatan menunjukkan adanya peningkatan kapasitas produksi dari sekitar 20 menjadi 80 kemasan per hari dengan efisiensi waktu hingga 60%. Mitra juga mampu melakukan pencatatan keuangan sederhana, menghitung harga pokok produksi, serta memisahkan keuangan usaha dan rumah tangga. Selain itu, telah terbentuk identitas merek, kemasan yang lebih informatif, serta pemanfaatan marketplace sebagai sarana pemasaran. Kesimpulannya, program ini efektif dalam meningkatkan produktivitas, tata kelola usaha, dan daya saing UMKM pangan lokal melalui integrasi teknologi, manajemen, dan digitalisasi pemasaran yang berkelanjutan.